Lightweight Strategies for Wooden-Structure Buildings Based on Embodied Carbon Emission Calculations for Carbon Reduction - Yukun Zhai; Yunan Li; Su Tang; Yixuan Liu; Yazhuo Liu (Buildings)
To achieve carbon reduction in architecture, this study establishes a carbon emission calculation model for wooden structures based on life cycle assessment (LCA) theory, using the emission factor method. Carbon emission factors involved in the entire life cycle of wooden buildings are identified and calculated for two modern wooden structures at Beijing Forestry University. The results are quantified and compared to analyze the causes of high carbon emissions, and lightweight design strategies for wooden structures are proposed through case studies. The two case buildings consumed 0.36 m3 and 0.29 m3 of wood material per square meter of building area, with carbon emissions of 311.23 kgCO2e/m2 and 292.03 kgCO2e/m2, respectively. During the building life cycle, waste disposal, material production, and material transportation accounted for the highest carbon emissions, accounting for 40%, 25%, and 20%, respectively. This study shows that factors such as the building shape coefficient, structural design, component design, material type, and decoration influence material usage in wooden structures, thereby affecting carbon emissions. Key strategies for reducing embodied carbon include optimizing building shape and structural design, using lightweight materials, and minimizing decoration.